Agro-Wellness Tourism As A Sustainable Rural Tourism Strategy: Opportunities And Challenges - Komang Trigita Juliastari; Ni Nyoman Deni Ariyaningsih; I Gusti Ayu Melistyari Dewi; Komang Shanty Muni Parwati; Firlie Lanovia Amir (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
Agro-wellness tourism has emerged as an innovative approach in sustainable rural tourism that integrates agricultural activities, wellness experiences, and local cultural values. This study aims to explore the potential and challenges of agro-wellness tourism development in rural Bali through a systematic literature review approach. Data were collected from reputable academic databases, including Google Scholar, Scopus, ScienceDirect, and Garuda, using keywords related to agro-wellness tourism, rural tourism, and sustainable tourism development. A total of selected literature was analyzed using qualitative content analysis with thematic synthesis to identify key patterns and insights. The findings indicate that Bali has significant potential for developing agro-wellness tourism due to its unique agricultural landscape, particularly the Subak system, as well as its strong cultural and spiritual traditions. Agro-wellness tourism contributes to rural economic diversification, job creation, and the strengthening of local micro-enterprises, while also supporting environmental conservation and cultural preservation. However, several challenges remain, including limited infrastructure, inadequate human resource capacity, weak digital promotion, and insufficient stakeholder collaboration. In addition, there are potential risks related to cultural commodification and environmental degradation if development is not properly managed. This study contributes to the literature by positioning agro-wellness tourism as an integrated rural tourism model that connects agriculture, wellness, and cultural experiences within a sustainable development framework. The findings provide implications for policymakers and tourism stakeholders in designing more inclusive, innovative, and sustainable rural tourism strategies in Bali.